Emerging Role of Mitophagy in the Heart: Therapeutic Potentials to Modulate Mitophagy in Cardiac Diseases. (23rd September 2021) - Luan, Yi; Luan, Ying; Feng, Qi; Chen, Xing; Ren, Kai-Di; Yang, Yang
Abstract : The normal function of the mitochondria is crucial for most tissues especially for those that demand a high energy supply. Emerging evidence has pointed out that healthy mitochondrial function is closely associated with normal heart function. When these processes fail to repair the damaged mitochondria, cells initiate a removal process referred to as mitophagy to clear away defective mitochondria. In cardiomyocytes, mitophagy is closely associated with metabolic activity, cell differentiation, apoptosis, and other physiological processes involved in major phenotypic alterations. Mitophagy alterations may contribute to detrimental or beneficial effects in a multitude of cardiac diseases, indicating potential clinical insights after a close understanding of the mechanisms. Here, we discuss the current opinions of mitophagy in the progression of cardiac diseases, such as ischemic heart disease, diabetic cardiomyopathy, cardiac hypertrophy, heart failure, and arrhythmia, and focus on the key molecules and related pathways involved in the regulation of mitophagy. We also discuss recently reported approaches targeting mitophagy in the therapy of cardiac diseases.